2015
DOI: 10.1371/journal.pone.0120632
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and the Relationship with Metabolic Syndrome in Chinese Aged Workers

Abstract: BackgroundShift work is indicated to be associated with adverse metabolic disorders. However, potential effects of shift work on metabolic syndrome (MetS) and its components have not been well established.MethodsIn total, 26,382 workers from Dongfeng-Tongji Cohort were included in this study. Information on shift work history was gathered through questionnaires and metabolic traits were measured. Logistic regression models were used to calculate the odds ratio (OR) and 95% confidence interval (CI) for long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
4
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 43 publications
(60 reference statements)
3
37
4
7
Order By: Relevance
“…This finding is in contrast to results from a meta-analysis that reported 10 or more years of shift work increased the risk of metabolic syndrome by 77% 2. Furthermore, a dose–response relationship between increasing years of shift work history and metabolic syndrome was found among women in a recent large study of Chinese workers, where every 10 years of shift work increased the OR for metabolic syndrome by 10% 29. It is possible that our study was underpowered, did not include enough variability in cumulative shift work exposure to detect a difference, or our comparator group included employees with other unmeasured personal or work characteristics that contributed to cardiometabolic risk.…”
Section: Discussioncontrasting
confidence: 89%
“…This finding is in contrast to results from a meta-analysis that reported 10 or more years of shift work increased the risk of metabolic syndrome by 77% 2. Furthermore, a dose–response relationship between increasing years of shift work history and metabolic syndrome was found among women in a recent large study of Chinese workers, where every 10 years of shift work increased the OR for metabolic syndrome by 10% 29. It is possible that our study was underpowered, did not include enough variability in cumulative shift work exposure to detect a difference, or our comparator group included employees with other unmeasured personal or work characteristics that contributed to cardiometabolic risk.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly however, previous studies consistently report little or no difference between the dietary intake of shiftworkers and non-shiftworkers [1,9,25,26] although the frequency and timing of meals is very potently disturbed, [26] and the risk of shiftworkers having metabolic syndrome was associated with the timing of meals but not with overall energy intake. [25] Human circadian rhythms in glucose and insulin sensitivity are optimised towards ingestion of food in daytime, yet shiftwork often necessitates that food is ingested at night when these endogenous metabolic rhythms are not prepared for food.…”
Section: Discussionmentioning
confidence: 92%
“…Keywords circadian depression diabetes neuroticism nightshift obesity shiftwork well being BACKGROUND Shiftwork is associated with detrimental effects on health and wellbeing, including increased risk of diabetes [1][2][3][4][5] and sleep problems, [6][7][8] higher body mass index (BMI) [1,[9][10][11][12], and increased signs of anxiety and depression. [8,13,14] Shiftworkers were once predominantly male, manufacturing sector workers, but this is no longer the case; a recent government survey reported that security services, transport and communications industries were the most common occupation of shiftworkers in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its retrospective design, the study does not include potentially confounding variables such as shift work, which is considered a risk factor for hypertension, insulin resistance, obesity, and dyslipidaemia. [35][36][37] It has been suggested that shift work may cause a rise in BP or cause progression of hypertension [38][39][40][41][42] ; however, this is not supported by more recent studies. [43][44][45] Nevertheless, not including shift work as a confounding factor may be considered as a limitation and we recognize the need for controlling for shift work in future research on the subject.…”
mentioning
confidence: 99%